Oceanography and Marine Biology 2017
DOI: 10.1201/b21944-4
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Dominance Along Rocky Shores, with a Focus on Intertidal Ascidians

Abstract: The role of dominant species is of central importance in ecology. Such species play a key role in ecosystem structure, stability and function, regulating resource allocation across trophic levels and overall ecosystem productivity. Although ecological interactions between dominant and subordinate species are often considered to influence the latter negatively, the presence of dominant species can also be beneficial. These species commonly act as ecosystem engineers and enhance biodiversity by creating habitat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 185 publications
(318 reference statements)
0
15
0
Order By: Relevance
“…In contrast, these taxa were usually present on a high proportion of the Ecosystem-wide shifts in diversity and abundance following the addition of structurally complex habitat have been well documented (e.g., Crooks, 1998). Ascidians in the genus Pyura can form thick bands on temperate rocky shores of the southern hemisphere (Rius et al 2017). Fauna occupying the interstices of beds of the closely related intertidal pyurid ascidian Pyura praeputialis (formerly P. stolonifera) has been examined in Southern Africa (Fielding, Weerts, & Forbes, 1994), South-Eastern Australia (Monteiro, Chapman, & Underwood, 2002) and Northern Chile-where they have invaded approximately 70 km of coastline at Antofagasta (Castilla et al, 2004;Cerda & Castilla, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, these taxa were usually present on a high proportion of the Ecosystem-wide shifts in diversity and abundance following the addition of structurally complex habitat have been well documented (e.g., Crooks, 1998). Ascidians in the genus Pyura can form thick bands on temperate rocky shores of the southern hemisphere (Rius et al 2017). Fauna occupying the interstices of beds of the closely related intertidal pyurid ascidian Pyura praeputialis (formerly P. stolonifera) has been examined in Southern Africa (Fielding, Weerts, & Forbes, 1994), South-Eastern Australia (Monteiro, Chapman, & Underwood, 2002) and Northern Chile-where they have invaded approximately 70 km of coastline at Antofagasta (Castilla et al, 2004;Cerda & Castilla, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Formerly known as P. stolonifera, molecular approaches have confirmed that this species is distributed from southern Queensland, down the Australian east coast to Victoria (Teske et al 2011, Rius & Teske 2013. Another species of the complex, Pyura doppelgangera, has recently been transported across Bass Strait from Tasmania and occupies some sites in the Victorian portion of the range of P. praeputialis (Rius et al 2017). Pyura praeputialis has also invaded the coast of Chile, occupying 70km of an embayment near Antofagasta (Castilla et al 2004).…”
Section: Study Organism and Study Locationmentioning
confidence: 99%
“…Pyura praeputialis (Heller, 1878) is a member of the Pyura stolonifera species complex, a group of at least 5 closely related and morphologically very similar solitary ascidian species (Rius et al 2017). Formerly known as P. stolonifera, molecular approaches have confirmed that this species is distributed from southern Queensland, down the Australian east coast to Victoria (Teske et al 2011, Rius & Teske 2013.…”
Section: Study Organism and Study Locationmentioning
confidence: 99%
See 2 more Smart Citations